Segway Line Tracer Using Proportional-Integral-Derivative Controllers - Wijaya Kurniawan; Mochammad Hannats Hanafi Ichsan; Eko Setiawan (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2016)
Intelligent control, sensors and hardware integration are expected to generate an efficient transportation system and and minimum effort, to carry goods from one location to another location. Line tracer used by robot to transport follow the path, it has a system that uses a light sensor to read the color from a line that represent the path to make specific direction. Segway is two wheeled transportation item that have an efficient energy used. Nowadays line tracer can only work if it has three or more wheels and segway can only work with riders. This research segway designed by lego robot, PID (Proportional, Integral, Derivative) control used to control an input from gyroscope sensor in form of elevation angle of the earth. The control system are expected to control two wheeled Segway to reach steady state rapidly. So the Segway would run without involving human or without rider.